2018
DOI: 10.1080/10888438.2018.1510936
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Awareness and Rapid Automatized Naming as Longitudinal Predictors of Reading in Five Alphabetic Orthographies with Varying Degrees of Consistency

Abstract: Although phonological awareness (PA) and rapid automatized naming (RAN) are confirmed as early predictors of reading in a large number of orthographies, it is as yet unclear whether the predictive patterns are universal or language specific. This was examined in a longitudinal study across Grades 1 and 2 with 1,120 children acquiring one of five alphabetic orthographies with different degrees of orthographic complexity (English, French, German, Dutch, and Greek). Path analyses revealed that a universal model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
187
4
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(251 citation statements)
references
References 68 publications
(76 reference statements)
30
187
4
10
Order By: Relevance
“…But the correlational results of initial RAN for colors suggest that more general automaticity components may be likewise relevant at early stages of word identification fluency. In this line, a recent report found RAN (average score of digits and colors) to be a consistent predictor of reading fluency from grade 1 to end of grade 2 across five alphabetic orthographies of varying complexity, including German (Landerl et al, 2019). Of note, gains in pseudoword reading in our study were not significantly correlated with T1 RAN skills, in line with the idea that pseudoword decoding relies on different processes than word identification.…”
Section: Benefits On Automaticity: Gains In Ran Skillssupporting
confidence: 88%
See 1 more Smart Citation
“…But the correlational results of initial RAN for colors suggest that more general automaticity components may be likewise relevant at early stages of word identification fluency. In this line, a recent report found RAN (average score of digits and colors) to be a consistent predictor of reading fluency from grade 1 to end of grade 2 across five alphabetic orthographies of varying complexity, including German (Landerl et al, 2019). Of note, gains in pseudoword reading in our study were not significantly correlated with T1 RAN skills, in line with the idea that pseudoword decoding relies on different processes than word identification.…”
Section: Benefits On Automaticity: Gains In Ran Skillssupporting
confidence: 88%
“…Finally, as mentioned in the introduction, orthographic transparency plays an important role in these differences. For instance, skills like RAN may relate to more universal mechanisms while the relative importance of phonological trainings may vary more with orthographic complexity (Landerl et al, 2019). Reading accuracy and pseudoword decoding, on the other hand, develop faster in transparent orthographies (Caravolas, 2018).…”
Section: Limitations and Implications For Future Grapholearn Versionsmentioning
confidence: 99%
“…100 It is a consistent predictor of reading fluency in various alphabetic 540 orthographies independently of their complexity. 104 RAN performance even predicts reading 541 performance at 2 years interval, 105 similarly well for reading performance assessed with tasks 542 tagging lexical and sublexical routes. It is thought that RAN and reading performances correlate 543 because both involve serial processing and oral production, 103 two processes that are common 544 to both reading routes.…”
Section: Classical Behavioral Predictors Related To Global Reading Abmentioning
confidence: 86%
“…Rapid automatized naming (RAN) is a process that in previous research, it has been found to correlate with reading ability both concurrently (e.g., Georgiou, Parrila, & Papadopoulos, ; Moll et al, ; Vaessen & Blomert, ) and over time (e.g., Georgiou, Papadopoulos, & Kaizer, ; Landerl et al, ; Lervåg & Hulme, ). However, findings are not consistent, and it is still not clear why and to what extent RAN relates to reading.…”
Section: Introductionmentioning
confidence: 99%